Pengembangan E-Commerce Penjualan Oleh-oleh Khas Lembata - Ricardo Oktavian Bala Deona; Tri Ana Setyarini (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Lembata’s traditional souvenirs represent a valuable combination of cultural heritage and local economic potential. Products such as handicrafts, titi corn, and dried fish are well-received commodities, yet their market reach remains limited due to the underutilization of digital technology. This study aims to explore the development of e-commerce as a strategy to expand the market for Lembata’s souvenirs. A qualitative descriptive method was employed through literature review, observation, and interviews. The system was developed using the Waterfall model and implemented with PHP and MySQL. The findings indicate that e-commerce can improve transaction efficiency, broaden promotional reach, and support the preservation of local culture. In addition, digital platforms allow consumers to access products without visiting physical stores. These results imply that successful implementation of digital marketing systems requires training for local business actors, better infrastructure, and cross-sector support to ensure long-term sustainability.